A fun and informative Open Access event? - Malovic, Ivana; Søyland, Marte J.; Werner, Tarjei F.; Vågnes, Nikolai; Skagen, Therese (Septentrio Conference Series, 2020)
Introduction The Norwegian research council supports the European cOAlition S, demanding that all scientific articles from the research they finance is openly available from 01.01.20211. Since 2013 the University of Oslo have mandatory institutional archiving of all peer reviewed articles in post-print version (after peer review)2. In 2019 several “publish and read” agreements were established between different publishers and the Norwegian higher education sector, enabling article processing charges to be paid by Norwegian universities and research institutions3. New agreements and changing regulations might be difficult to grasp by students, faculty and library employees. Aim is to test out basic knowledge about Open Access (OA) among beforementioned groups through a short, fun and informative OA event, while asking: Can a board game help promote Open Access? Method Choosing an existing OA board game was done based on the following considerations: it must have a recognizable concept and simple rules, be easy to administer, and not be too time consuming. Our choice is “The Game of Open Access”, a game produced by McGuinn and Spikin at University of Huddersfield, UK4. Modification of questions and answers to better fit a Norwegian context and publishing rules at the University of Oslo was essential. After testing of the game between us, minor alterations to the playing rules were added. Just as in the original game, for each correctly answered question, a participant keeps a card. After completing a round, the player gets a token representing a single published article, and then continues the game. The game is finished after all questions are answered correctly. The winner is the participant with the most points. Each card is worth three points and each token one point. These small modifications make the game more balanced and all participants equally involved. Before playing the game, a short (five minutes) introduction to OA in Norway with presentation of infographics is given. After the game, an evaluation form is administrated among all participants as an online questionnaire. Gameplaying time is approximately 30 minutes, which makes the game perfect for shorter events. Results Result from the evaluation form administered to librarians, students and faculty will be collected in the period September 2019-April 2020, in a range of different events. The first findings show that players are satisfied with board game content and questions, but they also suggest certain improvements Discussion Can a board game learning activity taking place outside of the ordinary library instructional courses for students and faculty at the University be an asset spreading awareness about Open Access? Does library staff have the basic understanding of the topic, or is further training needed?